2022
DOI: 10.3390/ijerph192214897
|View full text |Cite
|
Sign up to set email alerts
|

Planktothrix agardhii versus Planktothrix rubescens: Separation of Ecological Niches and Consequences of Cyanobacterial Dominance in Freshwater

Abstract: Cyanobacteria dominate lakes under diverse trophic conditions. Of these, two harmful filamentous cyanobacterial species, namely Planktothrix agardhii and P. rubescens, occupy completely different ecological niches in which they can form dense populations. In the present study, we investigated the effects of environmental conditions on the growth and vertical distribution of these species in lakes of different trophic statuses. Moreover, we underscored certain inconveniences in the assessment of the ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 70 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…As a result of these changes, the ratio between the mainly represented taxonomic groups of algae and cyanobacteria, forming the phytoplankton in freshwater basins, has also changed in recent years. It has been reported that cyanobacteria are a dominant group in many water bodies [ 56 , 57 , 58 , 59 , 60 , 61 ]. In some water bodies, there is even a displacement of the Chlorophyta, which traditionally occupy the first place in the phytoplankton of freshwater basins, by representatives of cyanobacteria [ 57 , 60 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these changes, the ratio between the mainly represented taxonomic groups of algae and cyanobacteria, forming the phytoplankton in freshwater basins, has also changed in recent years. It has been reported that cyanobacteria are a dominant group in many water bodies [ 56 , 57 , 58 , 59 , 60 , 61 ]. In some water bodies, there is even a displacement of the Chlorophyta, which traditionally occupy the first place in the phytoplankton of freshwater basins, by representatives of cyanobacteria [ 57 , 60 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria strains from the Planktothrix genus are the main focus of this investigation. P. agardhii (formerly Oscillatoria agardhii) and P. rubescens (formerly Oscillatoria rubescens) possess similar morphological organization, featuring trichome structures [64][65][66] . However, morphological taxonomic distinction is possible by their differing photosynthetic pigments.…”
Section: Planktothrixmentioning
confidence: 99%
“…P. agardhii characteristically presents as a blue-green hue generated from its phycocyanin production. P. rubescens prominently generates red phycoerythrin, a phenotype that P. agardhii lacks entirely 61,66 . Both filamentous species are devoid of heterocysts and possess gas vesicles that facilitate buoyancy migration in aquatic environments.…”
Section: Planktothrixmentioning
confidence: 99%
See 2 more Smart Citations